Accelerating Ice Loss From Peripheral Glaciers in North Greenland - Shfaqat A. Khan; William Colgan; Thomas A. Neumann; Michiel R. van denBroeke; Kelly M. Brunt; Brice Noël; Jonathan L. Bamber; Javed Hassan; Anders A. Bjørk (Geophysical Research Letters)
Abstract In recent decades, Greenland's peripheral glaciers have experienced large‐scale mass loss, resulting in a substantial contribution to sea level rise. While their total area of Greenland ice cover is relatively small (4%), their mass loss is disproportionally large compared to the Greenland ice sheet. Satellite altimetry from Ice, Cloud, and land Elevation Satellite (ICESat) and ICESat‐2 shows that mass loss from Greenland's peripheral glaciers increased from 27.2 ± 6.2 Gt/yr (February 2003–October 2009) to 42.3 ± 6.2 Gt/yr (October 2018–December 2021). These relatively small glaciers now constitute 11 ± 2% of Greenland's ice loss and contribute to global sea level rise. In the period October 2018–December 2021, mass loss increased by a factor of four for peripheral glaciers in North Greenland. While peripheral glacier mass loss is widespread, we also observe a complex regional pattern where increases in precipitation at high altitudes have partially counteracted increases in melt at low altitude.